Revisit the Development of Native Indonesian Chickens from Red Jungle Fowls (Gallus gallus bankiva) to Commercial Chickens - Moh Hasil Tamzil; B Indarsih (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Kampung chicken which is one of native Indonesian chickens has been domesticated from the ancestor of Red Fowl Jungle, and developed by the village community from generation to generation through an extensive rearing method. Before the intensive management of kampung chicken was introduced, the chickens were allowed to scavange around the household yard during the day, they slept in the trees, on the roofs or underneath of the household at night. It has been for many years that kampung chickens were crossed with imported exotic breeds, and unplanned selection. As a result, kampung chickens have developed to a considerable high phenotype and genetic varieties with several different names and purposes. There have been selection programs, which have resulted a considerable strain of improved egg type of Kampung chicken (KUB-1 chicken), and a strain of broiler type of local chicken (Sensi-1 Agrinak chicken and Gaoksi chicken). KUB-1 chickens can be used as female lines, and Sensi-Agrinak and Gaoksi chickens can be used as male lines to produce local commercial broilers. The article is to provide information on the domestication process of Red Jungle Fowl chickens into Kampung chickens and their development to become layer and broiler line chickens.